Survey of medicinal plants and patterns of knowledge in district Swabi/ Khyber Pakhtunkhwa, Pakistan - Abdul Waheed; Ali Bahadur; Abdul Majid; Fahad Nasir; Mohib Shah; Asfa Batool (International Journal of Phytomedicine, 2018)
To investigate and document the indigenous knowledge on the medicinal flora of the native communities in Swabi district, Pakistan. A field survey was carried out and data was based on semi-structured interviews, group discussions, and questionnaire from 8 villages. 180 local individual of local communities were interviewed and collected data were analyzed by quantitative and descriptive index. During the survey, 81 species belonging to 45 families were reported. Solanaceae was the leading family with 7 species. Herb (48%) was the dominant plant habit and leaf (24%) was the most preferred used part for indigenous medicine. Moreover, decoction (28.93%) was the most prestigious method. According to the result, the highest use value was documented for Jaundice ailment (1.00-0.81). Besides, 11 plants added to the endangered species list. Local experts of Swabi district practice a huge variety of ethnomedicinal plants in treating a wide spectrum of disorders, especially those plants used to cure jaundice. Our finding suggest that the pharmacological potential across some of these plants has been therapeutically validated however still need to explore the pharmacological properties of other species. Hence, the present investigation, aside from being a source of new insight for ethnobotanical and pharmacological cure of many disorders, might contribute to upgrade the sustainability, conservation, and management of medicinal flora in the Bachai Sikandari, district Swabi.